PENGARUH PENGGUNAAN MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BERWIRAUSAHA SISWA KELAS X PEMASARAN SMK KOMPUTAMA MAJENANG - Yogi Nurfauzi; Tri Almunawaroh; Nurul Febrinia Damayanti (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2023)
SMK students are expected to start a business. However, in reality students of SMK are not fully interested in entrepreneurship, this is due to students' lack of knowledge about entrepreneurship, fear of facing the risk of failure, lack of promotion ability, and limited time that students have. This study aims to find out: 1) The use of Instagram social media for Grade X Marketing SMK Komputama Majenang. 2) Entrepreneurship interest Grade X Marketing SMK Komputama Majenang. 3) The effect of using Instagram social media on the entrepreneurship interest at Grade X Marketing SMK Komputama Majenang. This research has used a quantitative approach and the type of research was causality. The population of this study was 50 students with a sample of 25 students. Data collection techniques using interviews and questionnaires. The data analysis technique used was descriptive statistics and simple regression analysis. The results obtained: 1) The use of Instagram social media for Grade X Marketing SMK Komputama Majenang, which is in the low category is 20%, the medium category is 76% and the high category is 4%. 2) The interest in entrepreneurship for Grade X Marketing SMK Komputama Majenang, which is in the low category is 16%, the medium category is 84% and the high category is 0%. 3) There is an effect of the use of Instagram social media on the entrepreneurship interest at Grade X Marketing SMK Komputama Majenang by 61.4%.